2015
DOI: 10.1016/j.vph.2015.08.014
|View full text |Cite
|
Sign up to set email alerts
|

Diminazene enhances stability of atherosclerotic plaques in ApoE-deficient mice

Abstract: Angiotensin (Ang) II contributes to the development of atherosclerosis, while Ang-(1–7) has atheroprotective actions. Accordingly, angiotensin-converting enzyme 2 (ACE2), which breaks-down Ang II and forms Ang-(1–7), has been suggested as a target against atherosclerosis. Here we investigated the actions of diminazene, a recently developed ACE2 activator compound, in a model of vulnerable atherosclerotic plaque. Atherosclerotic plaque formation was induced in the carotid artery of ApoE-deficient mice by a shea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 54 publications
2
21
0
Order By: Relevance
“…Our previous studies demonstrated that plaques in these vessel segments exhibited advanced features and resembled vulnerable and stable plaque phenotypes, respectively [716]. In the vessel segment upstream of the cuff outside of the plaque region, LSI was the dominant metric.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Our previous studies demonstrated that plaques in these vessel segments exhibited advanced features and resembled vulnerable and stable plaque phenotypes, respectively [716]. In the vessel segment upstream of the cuff outside of the plaque region, LSI was the dominant metric.…”
Section: Discussionmentioning
confidence: 92%
“…Plaques were present over nearly the entire downstream segment with an average length of 1.2 ± 0.1 mm. Previous work established that plaques upstream of the cuff have vulnerable features, whereas those downstream more closely resemble stable lesions [716].
Figure 3.Representative histological sections from the instrumented and contralateral control arteries of a representative mouse at nine weeks, stained for lipids.
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…ApoE −/− male mice in C57BL/6J background (n = 40) were purchased from Jackson Laboratories (Les Oncins, France) and, at 15 weeks old, received Western‐type diet consisting of 15% (wt/wt) cocoa butter and 0.25% (wt/wt) cholesterol (Diet W; abDiets) for the entire experimental period of 11 weeks. Atherosclerotic plaques with different phenotypes were induced in the carotid artery by modifying the local pattern of shear stress as previously described . Briefly, after a 2‐week western diet adaptation period, a shear stress modifier device, called “cast,” was placed around the right carotid artery.…”
Section: Methodsmentioning
confidence: 99%
“…Immunohistochemistry was performed to assess the intraplaque expression of MMP‐9, as well as macrophage and neutrophil infiltration. As described elsewhere, LSS‐ and OSS‐carotid regions and aortic sinus were serially cut in 7 μm transverse sections (11 sections per staining separated by 45 μm from each other), fixed in acetone and immunostained with specific antibodies: anti‐mouse MMP‐9 (dilution: 1:60; R&D Systems), anti‐mouse CD68 (macrophages, dilution: 1:400; ABD Serotec, Dusseldorf, Germany) and anti‐mouse Ly‐6B.2 (neutrophils, dilution: 1:50; ABD Serotec). Quantitative analysis was performed with MetaMorph software.…”
Section: Methodsmentioning
confidence: 99%